Moral foundations are better predictors of belief in COVID-19 conspiracy theories than the Big Five personality traits - Nejat, Pegah; Heirani-Tabas, Ali; Nazarpour, Mohammad Mahdi (Frontiers in Psychology, 2023)
Upon the sudden outbreak of COVID-19 pandemic, various conspiracy theories regarding the virus proliferated in the social media. This study focused on the sociodemographic, personality, and moral predictors of these beliefs. More specifically, we asked whether moral values predict belief in COVID-19 conspiracy theories over and above sociodemographic variables and the Big Five personality traits. According to Moral Foundations Theory, five cross-cultural moral foundations are more broadly categorized under individualizing (Care & Fairness) and binding (Loyalty, Authority, & Sanctity) foundations. A sixth moral foundation was Liberty which we included along with binding and individualizing foundations. Participants were 227 Iranians (mean age = 31.43, SD = 12.61, 75.3% female) who responded to Moral Foundations Questionnaire and Liberty items, a range of COVID-19 conspiracy beliefs, and the 10-Item Personality Measure of the Big Five. Among demographic variables, religiosity and socioeconomic status were the strongest determinants of conspiracy beliefs regarding the origin of Coronavirus. Among the Big Five, only extraversion predicted these beliefs in a positive direction. Moral foundations, most notably Authority and Sanctity, showed incremental predictive power over both demographic variables and the Big Five personality traits. Findings are discussed in light of the role of social media in dissemination of conspiracy beliefs regarding the pandemic. They point to the more relevance of moral foundations, particularly binding foundations, than the Big Five in the context of pandemic-related conspiracy beliefs, and add to the literature on the unique contribution of moral foundations to socio-political attitudes across cultures.